Peran Media Sosial Dalam Membangun Kesadaran Masyarakat Terhadap Kerusakan Lingkungan: Analisis Praktik Komunikasi Lingkungan digital - Suci, Tari Setia; Yolanda, Selfia; Daramika, Suci (Sagita Academia Journal, 2025)
The rapid development of social media has changed the way individuals obtain information, form opinions, and take action, including on environmental issues. This study examines the influence of digital campaigns on social media on increasing environmental awareness and environmentally friendly behavior. Through an analysis of digital campaign content and a survey of active social media users, it was found that social media plays a significant role in environmental education and advocacy. Creative, interactive, and evidence-based campaign content has been shown to be more effective in influencing attitudes and actions, such as reducing the use of single-use plastics, managing waste, and choosing environmentally friendly products. The results show that active participation in digital campaigns not only increases knowledge but also strengthens social norms that encourage collective behavioral change. However, campaign effectiveness is influenced by trust in the information source, digital literacy levels, and the consistency of the message. This study underscores the significance of collaboration among communities, environmental activists, and social media platforms in expanding the reach of campaigns and fostering sustainable behavioral change. Thus, social media can be a strategic tool in strengthening environmental movements in the digital era.